Spatial alignment and the motion bridging effect: Reversals in the direction of an illusory rotation - Maximilian Stein; Robert Fendrich; Uwe Mattler (i-Perception, 2025)
When a stationary ring of points precedes or follows an “inducing ring” of points that spins so rapidly it appears to be a steady outline circle the stationary ring often appears to momentarily rotate in the direction of the inducing ring's spin. In previous studies of this “motion bridging effect” (MBE) the start and stop positions of the inducing ring points were spatially aligned with the points of the stationary ring. Here we report that as these start and stop positions are progressively displaced across the spaces separating the points of the stationary test ring the MBE direction congruency effect decreases and then reverses, so that the illusory rotation is predominantly opposite to the direction of the inducing ring spin. This reverse congruency effect peaks when the points of the inducing ring start and stop midway between the points of the stationary test ring, with congruency returning as further displacements bring the point positions back into alignment. We conclude that the MBE is not only determined by the inducing ring's rotation direction, but also by an interaction between the inducing and test ring points at the moment the inducing ring starts or stops. We consider various ways of accounting this effect. Explanations based on direction cuing by apparent motion steps, the motion aftereffect, and biphasic impulse responses are ruled out. A speculative explanation based on perceptual heuristics that interpret the competing motion direction signals generated by a transformation of contour segments of the spinning ring into the points of the stationary ring (or vice-versa) is proposed.